A comparative pilot study on the effects of laser and light-emitting diode therapy on pain in individuals with temporomandibular disorder (Research, Society and Development, 2022)
Temporomandibular disorder (TMD) is described as a subgroup of orofacial pain. Studies have demonstrated that phototherapy is an effective treatment option for TMD, leading to improvements in pain and orofacial function. To compare the effects of photobiomodulation with different light sources on pain and functioning in patients with TMD. Methods: A randomized, controlled, double-blind clinical trial (pilot study) was conducted with 15 individuals aged 18 years or older allocated to two photobiomodulation groups: laser and LED. Sessions were held twice a week for four weeks (total: eight sessions). The Research Diagnostic Criteria for Temporomandibular Disorders were used for the evaluation and Pain was measured using the Visual Analog Scale. Orofacial function was determined based on measures of mandibular movements. Photobiomodulation was administered to the temporomandibular joint, masseter (upper, middle and lower) and anterior temporal muscles. Results: Statistically significant differences in pain were found in the intra-group analyses (pre-treatment vs. post-treatment) in both groups (laser: p=0.0117; LED: p=0.0180). Statistically significant intra-group differences were found for maximum mouth opening without assistance and maximum mouth opening with assistance in the laser group (p= 0.0203 and 0.0001, respectively). The same was found in the LED group only regarding maximum mouth opening with assistance (p=0.0459). Statistically significant intra-group differences (pre-treatment vs. post-treatment) were found for lateral excursion to both sides in the laser group (right side: p=0.0209; left side: p=0.0005) and only to the left side in the LED group (p=0.0342). Conclusion: Photobiomodulation with laser and LED produce similar effects regarding improvements in TMD.